ASSESSING THE POLITICAL CHALLENGES IN PROMOTING THE SUSTAINBLE DEVELOMENT GOAL OF ACCESS TO JUSTICE IN CAMEROON - Benjamin Enow Agbor (American Journals, 2022)
Sustainable Development Goal 16 Target 3 (SDG 16.3) seeks to promote Access to justice for all as a necessary catalyst for development. The commitment of Cameroon to pursue this goal has been expressed in policy, legal and institutional frameworks and efforts have been engaged to attempt to attain the goal. However, the objectives of the state are hampered by several factors. This paper explores the political challenges hampering this project. Adopting an interdisciplinary approach in the interpretation and content analysis of the primary and secondary sources and empirical evidence acquired through unstructured interviews, the study is inspired by the Triple Throng Theory of Henry Shue which requires the State to respect, protect and fulfil the human rights of its citizens, and the Rule of Law theory of A.V Dicey which propagates the need for an independent judiciary based on the separation of powers. The study argues that politics constitutes one of the greatest challenges to the full attainment of the goal of access to justice for all as the judicial arm of government is not independent. The study concludes that politics will continue to be a bane to the full attainment of access to justice in Cameroon by the year 2030.